Biosynthesis of Novel Pyoverdines by Domain Substitution in a Nonribosomal Peptide Synthetase of Pseudomonas aeruginosa - Calcott, Mark J. (American Society for Microbiology, 2014)
Pyoverdine is a fluorescent nonribosomal peptide siderophore made by fluorescent pseudomonads. The Pseudomonas aeruginosa nonribosomal peptide synthetase (NRPS) PvdD contains two modules that each incorporate an l-threonine residue at the C-terminal end of pyoverdine. In an attempt to generate modified pyoverdine peptides, we substituted alternative-substrate-specifying adenylation (A) and peptide bond-catalyzing condensation (C) domains into the second module of PvdD. When just the A domain was substituted, the resulting strains produced only wild-type pyoverdine—at high levels if the introduced A domain specified threonine or at trace levels otherwise. The high levels of pyoverdine synthesis observed whenever the introduced A domain specified threonine indicated that these nonnative A domains were able to communicate effectively with the PvdD C domain. Moreover, the unexpected observation that non-threonine-specifying A domains nevertheless incorporated threonine into pyoverdine suggests that the native PvdD C domain exhibited stronger selectivity than these A domains for the incorporated amino acid substrate (i.e., misactivation of a threonine residue by the introduced A domains was more frequent than misincorporation of a nonthreonine residue by the PvdD C domain). In contrast, substitution of both the C and A domains of PvdD generated high yields of rationally modified pyoverdines in two instances, these pyoverdines having either a lysine or a serine residue in place of the terminal threonine. However, C-A domain substitution more commonly yielded a truncated peptide product, likely due to stalling of synthesis on a nonfunctional recombinant NRPS template.